184k views
25 votes
The roots of a quadratic function are x = -3 and x = 2/3. Which of the following would be the constant term of the equation in standard form?

A. -2
B. 6
C. 2
D. -6

1 Answer

8 votes

Answer:

-2

Explanation:

Since the roots are known and the function is a quadratic function, we can write down the function:

y = (x+3)(x-2/3) since when the roots are plugged in, the function gives 0.

Standard form means that the function has to be expanded:

y = (x+3)(x-2/3) =
x^(2)+3x - 2x/3 - 3*2/3

y =
x^(2)+ 7x/3 - 2

The constant term is -2.

User Chris Rosete
by
4.6k points